Aplikasi Single Index Model dalam Pembentukan Portofolio Optimal Saham LQ45 dan Jakarta Islamic Index - Oktaviani, Berlian Nanda; Wijayanto, Andhi (Management Analysis Journal, 2016)
The aim of this study is to constructing optimal portfolio from LQ45 stocks and Jakarta Islamic Index stock in 2013-2015 as well as calculating the portfolio’s return, risk and it’s performance. Sample of this study are 29 listed companies from LQ45 and 19 listed companies from JII selected by purposive sampling method. This study applying Sharpe’s single index model to constructing an optimal portfolio and Jensen’s Index to measure the portfolio performance. The result of calculations using Sharpe’s single index model that includes the LQ45 optimal portfolio with the proportion of funds that of UNVR as 52.15%, AKRA as 28.77% and ICBP as 19.06%. The LQ45 portfolio has return as 1.77% along with risk as 2.73% with performance as 0.0147709. The portfolio formed from JII along with the proportion of funds is UNVR as 50.80%, AKRA as 27.63%, ICBP as 18.31%, WIKA as 3.97%. The JII portfolio has return as 1.77%, risk as 2.93% with performance 0.0150893. The conclusions of this study is to diversify with a single index model proved to be more favorable and unfavorable views of portfofolio performance compared to the performance of IHSG. Suggestion related to this study is conventional investor may pick LQ45 portfolio and Islamic investor may select JII portfolio as their investment policy.